글로벌 금융위기 이후 신용평가산업의 환경변화 고찰과 주요 현안에 대한 정책제안 - 오세경(Se Kyung Oh); 황인덕(In Deok Hwang) (한국증권학회지, 2012)
오늘날 글로벌 신용평가기관은 그 역할의 중요성에 대한 평가와는 별개로 부정적 기능에 대한 비판이 상당히 고조되고 있는 상황이다. 심지어 글로벌 금융위기를 야기한 배후요인으로 지목되기도 한다. 이러한 상황에서 G20를 중심으로 세계 각국은 신용평가기관에 대한 규제를 대폭 강화하고 있다. 본 연구는 먼저 글로벌 신용평가기관의 문제점은 무엇이며 이를 개선하고자 하는 국제적인 규제강화는 어떻게 이루어지고 있는지에 대해 살펴본다. 이어서 국내 신용평가산업의 현황과 주요 현안에 대해 살핀 후, 국내 신용평가기관과 글로벌 신용평가기관이 직면하고 있는 어려움이 어떻게 다르고 그에 따라 우리정부의 당면 현안에 대한 대응방안이 어떻게 달라져야 하는지를 다루고자 한다. 본 연구에서 다룬 중요 사안들은 다음과 같다. 첫째, 금융당국은 국제적 공조 차원에서 우리나라 신용평가기관에 대한 규제를 강화하는 방향으로 신용정보법을 개정하여 시행중인데 이에 대한 문제점과 개선방향을 제시한다. 둘째, 우리나라의 경우에 특히 문제가 되고 있는 회사채 발행에 있어서의 등급쇼핑과 등급인플레를 해결하기 위한 정책적 대안을 제시한다. 셋째, 최근 논의되고 있는 복수평가제의 폐지에 대한 올바른 정책 방향을 제시한다. 마지막으로 신용평가산업에 대한 진입을 완화하여 경쟁을 촉진시키는 것이 과연 바람직한 정책 방향인가에 대해 논한다. Although the role of Credit Rating Agencies (CRAs) is considered very important, there arose many blames on their negative functions after the recent global financial crisis. CRAs were even pinpointed as one of many culprits of the crisis. Under theses circumstances, G20 countries including US and European Union were strengthening the regulations on the credit rating industry. The paper analyzes the problems of global CRAs and new global regulations to tightly control them. After we illustrate current circumstances and major issues of Korean credit rating industry, we claim that Korean CRAs confront different problems and issues from those of global players and our regulatory authority should act differently from other countries. The paper provides policy suggestions on major issues of Korean credit rating industry:how to change credit information act, how to solve ‘rating shopping’ and ‘rating inflation’ problems, whether we should abolish the compulsory multiple rating system or not, and whether we should boost the competitions in the industry or not. KCI Citation Count: 24